Gas-Liquid Separator Modified on CV-AAS System for Determination of Total Hg in the Industrial Wastewater Samples - Sujito, Sujito; Pasaribu, Subur P; Wirawan, Teguh; Panggabean, Aman Sentosa (Universitas Jenderal Soedirman, 2022)
The research about the utilization of modified gas-liquid separators in the determination of Hg ions by using the Cold Vapor Atomic Absorption Spectrophotometer (CV-AAS) method has been done. To optimize the measurement results, several parameters that affect the hydride generator have been studied. Some specified essential parameters are the type and concentration of acid, the level of SnCl2 as a reducing agent, sample volume and the analytical performance such as linearity (r), detection limit (LOD) and quantitation limit (LOQ), repeatability (% RSD), and accuracy have been studied. The results of the research showed the gas-liquid separator modified can be used instead of commercial gas- liquid separators. It was showed by the repeatability value as % RSD < 2/3 CV Horwitz values, the LOD was 0.2530 μg/mL, and the LOQ was 0.8432 μg/mL. The accuracy of this method was good shown by a recovery percentage of 101.6%. Based on the result of this research, the modified of gas-liquid separator can be used for the determination https://www.adenomyosisadviceassociation.org/hysterectomy of Hg ions by using the CV-AAS method with valid results